The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1111/fcp.12460
|View full text |Cite
|
Sign up to set email alerts
|

Non‐steroidal anti‐inflammatory drug prescriptions from the 6th month of pregnancy: impact of advice from health authorities

Abstract: Non‐steroidal anti‐inflammatory drugs (NSAIDs) are among the most widely used drugs. On June 2008 and February 2009, Dear Doctor Letters (DDLs) were sent by the French Health Authorities (AFSSAPS) to remind practitioners of risks with NSAIDs after the fifth month of pregnancy. The aim of this study was to evaluate the impact of these letters on NSAID prescriptions during late pregnancy. EFEMERIS is a French database that registers drugs prescribed and reimbursed during pregnancy and outcomes between 2004 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…There is unclear data about HCPs awareness of DHPC [5,6]. Besides, the successful delivery of DHPC to HCP, its clarity, and its effectiveness in changing the prescribing practice of targeted HCPs is still questionable [7]; few studies revealed that DHPCs were suitable in conveying the required message and affecting the HCP's behavior [8][9][10], however, the majority of conducted studies showed several defects in such risk communication tool, ranging from the fact that it did not actually reach the target HCPs [4,11], to its poor ability in communicating the required data [12,13]. Hence, some studies recommended the use of an additional method with DHPC for better risk communication.…”
Section: Introductionmentioning
confidence: 99%
“…There is unclear data about HCPs awareness of DHPC [5,6]. Besides, the successful delivery of DHPC to HCP, its clarity, and its effectiveness in changing the prescribing practice of targeted HCPs is still questionable [7]; few studies revealed that DHPCs were suitable in conveying the required message and affecting the HCP's behavior [8][9][10], however, the majority of conducted studies showed several defects in such risk communication tool, ranging from the fact that it did not actually reach the target HCPs [4,11], to its poor ability in communicating the required data [12,13]. Hence, some studies recommended the use of an additional method with DHPC for better risk communication.…”
Section: Introductionmentioning
confidence: 99%